Investment Decision Using Capital Asset Pricing Model (CAPM) in Oil & Gas Production & Refinery Sectors - Dwiputri, Sarastika (Journal of Entrepreneurship, Management and Industry (JEMI), 2024)
The primary objective of this study was to explore the utilization of the Capital Asset Pricing Model (CAPM) technique in the analysis of investment decisions, specifically within the Oil & Gas Production & Refinery Sector. Five stocks belonging to this sector were selected for examination, all of which are publicly traded on the Indonesian Stock Exchange (IDX). The study period encompassed November 2022 to October 2023, and the chosen stocks were Astrindo Nusantara Infrastruktur Tbk, Energi Mega Persada Tbk, Medco Energi Internasional Tbk, Super Energy Tbk, and Mitra Investindo Tbk. In this research, linear regression analysis was employed to determine the beta coefficient for the Capital Asset Pricing Model (CAPM) method. This allowed for a comparison between the anticipated returns and the stock market's rate of return during the observation period. The aim was to distinguish between undervalued and overvalued stocks. Data for this analysis was sourced from www.yahoo.finance.com The findings of the study revealed that four out of the five companies within the Oil & Gas Production & Refinery Sector exceeded the expected returns, indicating that they were undervalued or considered efficient. These companies were Astrindo Nusantara Infrastruktur Tbk, Energi Mega Persada Tbk, Super Energy Tbk, and Mitra Investindo Tbk. On the other hand, Medco Energi Internasional Tbk was categorized as overvalued or inefficient.